2013
DOI: 10.1097/shk.0b013e31829635cf
|View full text |Cite
|
Sign up to set email alerts
|

Role of RhoA in Regulating the Pump Function of Isolated Lymphatics From Hemorrhagic Shock Rats

Abstract: The aim of this present study was to examine changes in RhoA protein levels and the role in RhoA in lymphatic contractility and reactivity after hemorrhagic shock. Levels of RhoA and phospho-RhoA in lymphatic tissue isolated from hemorrhagic shock rats were measured, and the contractility and reactivity to substance P of lymphatics isolated from control rats and rats subjected to shock 0.5 and 2 h were determined with an isolated lymphatic perfusion system at a transmural pressure of 3 cmH2O. At the same time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…These results of lymphatic contractility and reactivity following hemorrhage and resuscitation were similar with that of lymphatics from hemorrhagic shock without resuscitation in previous report 6 . Because lymphatic pumping plays a vital role in the regulation of interstitial fluid volume 12 , therefore, the treatment of enhancing lymphatic pump function may be beneficial to hemorrhagic shock.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…These results of lymphatic contractility and reactivity following hemorrhage and resuscitation were similar with that of lymphatics from hemorrhagic shock without resuscitation in previous report 6 . Because lymphatic pumping plays a vital role in the regulation of interstitial fluid volume 12 , therefore, the treatment of enhancing lymphatic pump function may be beneficial to hemorrhagic shock.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies demonstrated that lymphatic reactivity to vasoactive substances is associated with lymphatic contractile activity 5,6,10,11 . Therefore, in this study, furthermore, we tested the isolated lymphatic contractile response to gradient concentration of SP, and found that the difference value of indexes of CF, TI and FPF decreased at certain concentrations of SP, significantly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations